Waste glass activity rapid comprehensive evaluation method based on dissolution kinetics analysis
Through a rapid evaluation method based on kinetic analysis, the dissolution characteristics of waste glass in an alkaline environment were measured, and the corresponding relationship between particle size-reaction rate-activity index was established, which solved the problems of long test cycles and poor results stability in the prior art, and achieved rapid and accurate evaluation of waste glass activity.
Patent Information
- Application Number
- CN202411994765.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing waste glass activity evaluation methods have problems such as long testing cycles and poor results stability, which are difficult to meet the rapid and accurate resource utilization needs of waste glass in the field of building materials.
Using a rapid evaluation method based on kinetic analysis, the silicon ion dissolution characteristics of waste glasses of different particle sizes in alkaline environments was determined, and the corresponding relationship between the dissolution kinetic parameters and the 28d activity index was established to achieve rapid and accurate evaluation of waste glass activity.
The test cycle was shortened from the traditional 28 days to 24 hours, which improved the detection efficiency and established a scientific and complete "particle size-reaction rate-activity index" evaluation system. The stability and accuracy of the results were significantly improved, and it was suitable for the evaluation of waste glass activity from different sources and components.
Smart Images

Figure CN119780070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material detection, and in particular to a method for rapid comprehensive evaluation of waste glass activity based on kinetic analysis. Background Art
[0002] With the acceleration of urbanization and the improvement of living standards, the amount of waste glass produced is showing a rapid growth trend. According to statistics, more than 200 million tons of waste glass are produced worldwide each year, of which about 40% comes from building demolition and domestic waste. The treatment and resource utilization of waste glass has become a global environmental issue.
[0003] At present, the main treatment methods for waste glass include direct landfill, recycling and remelting, and utilization as building materials. Among them, direct landfill not only occupies a large amount of land resources, but also has a long-term impact on the soil due to the difficulty of glass degradation, resulting in serious waste of resources. Recycling and remelting is also an important traditional treatment method, but it has high energy consumption, high cost, and produces a large amount of greenhouse gases, causing secondary pollution.
[0004] At present, the mainstream method for evaluating the activity of waste glass is based on GB / T 1596-2017 "Fly ash used in cement and concrete". This method evaluates its activity by measuring the 28-day compressive strength ratio of cement mortar mixed with waste glass powder. This method has obvious limitations: first, the test cycle is as long as 28 days, which seriously affects production efficiency and raw material quality control; second, the strength ratio index is affected by many factors, such as water-cement ratio, curing conditions, test errors, etc., resulting in poor stability of the results; third, this method only reflects the final strength contribution of the material, and cannot reveal the activity evolution law of waste glass during the hydration process.
[0005] In engineering applications, due to the lack of a fast and accurate activity evaluation method, the activity evaluation results are often out of touch with the actual effects, which increases the difficulty of quality control and makes the mix design lack a scientific basis. At present, related research at home and abroad mainly focuses on the physical and chemical properties of waste glass, and its activity mechanism is insufficient. A systematic evaluation system has not yet been formed, and the degree of standardization is low. This situation seriously restricts the large-scale application of waste glass in the field of building materials.
[0006] In view of the importance of waste glass resource utilization and the shortcomings of existing technologies, it is of great theoretical significance and practical value to develop a scientific, rapid and accurate method for evaluating the activity of waste glass. The evaluation method based on silicon ion dissolution proposed in the present invention establishes a quantitative activity evaluation system by measuring the dissolution characteristics of silicon ions in waste glass under alkaline environment, which can effectively solve the problems existing in the existing technologies and provide reliable technical support for the resource utilization of waste glass. Summary of the invention
[0007] The present invention aims to solve the problems of long test cycle and poor result stability in the existing waste glass activity evaluation methods, and proposes a rapid evaluation method based on kinetic analysis. By studying the dissolution characteristics of waste glass with different particle sizes, the corresponding relationship between the dissolution kinetic parameters and the 28d activity index is established, so as to achieve rapid and accurate evaluation of the activity of waste glass.
[0008] The purpose of the present invention is achieved by at least one of the following technical solutions.
[0009] The method adopted by the present invention comprises the following steps:
[0010] 1. Waste Glass Sample Preparation
[0011] First, the waste glass is pretreated, cleaned and surface impurities are removed, and then dried in an electric blast drying oven at 105±5℃ for 24 hours to constant weight, and then crushed using a jaw crusher.
[0012] Then the powder was ground using a ball mill with a ball-to-material ratio of 4:1. By controlling the grinding time, samples with different particle sizes were obtained, including five specifications of 6μm, 11μm, 19μm, 25μm, and 38μm. The D 50 To ensure that the particle size meets the requirements, the ground sample is dried at 105±5℃ for 2h.
[0013] Finally, the component analysis was carried out, and the chemical composition was determined by X-ray fluorescence spectrometer (XRF), and the contents of main oxides such as SiO2, Al2O3, CaO, and Na2O were recorded.
[0014] 2. Dissolution test
[0015] When preparing the solution, first weigh analytical pure NaOH, prepare it into a 4 mol / L solution with deionized water, and cool it to the test temperature at room temperature.
[0016] The test conditions are as follows: the solid-liquid ratio is strictly controlled to 1:300-1:600 g / mL, 1.0000±0.0005 g of waste glass powder is accurately weighed, and 500±1 mL of NaOH solution is added. The test is carried out at 40°C, and the magnetic stirring speed is controlled at 1000±50 rpm.
[0017] Sampling was performed at the specified time points, including 0.25h, 0.5h, 1h, 3h, 6h, 12h, and 24h. 10mL of sample was taken each time, filtered using a 0.45μm filter membrane, and then diluted with a 5wt.% nitric acid solution, with the dilution multiple selected from 10 to 50 times according to the concentration. The diluted samples were stored in a refrigerator at 5±1℃.
[0018] 3. Kinetic Analysis
[0019] ICP-OES was used to determine the silicon ion concentration in the filtrate and the silicon dissolution rate at different time points was calculated. Kinetic analysis of the dissolution data was performed:
[0020] The apparent first-order reaction kinetic equation is adopted:
[0021] ln(1-α)=-kt
[0022] Where: α is the silicon dissolution rate, t is the reaction time (h), and k is the reaction rate constant (h-1).
[0023] For samples with different particle sizes, the reaction rate constant k is calculated by fitting. Studies have shown that there is a power function relationship between the k value and the particle size d:
[0024] k=A*d -n
[0025] Where A and n are fitting constants.
[0026] 4. Compressive strength test
[0027] The raw materials used were P·II 42.5 ordinary Portland cement, ISO standard sand, waste glass powder prepared according to step 1, and laboratory tap water.
[0028] The mix design adopts the following mass ratios: water-cement ratio 0.5, sand-cement ratio 3, and waste glass powder replaces cement 20%-40%, preferably 30%. The specimens were prepared according to the requirements of GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", and 40mm×40mm×160mm specimens were made, with 3 parallel specimens prepared in each group. The stirring was slow for 120±5s and fast for 120±5s. After the specimens were formed, they were immediately covered with plastic film, demolded after 24±2h, and standard curing was carried out at a temperature of 20±2℃ and a relative humidity of ≥95%.
[0029] After 28 days of curing, the compressive strength test was carried out according to the test method of GB / T 1596-2017 "Fly ash used in cement and concrete". The average value of three specimens was taken, and the activity index K was calculated as (strength of specimen mixed with 30% waste glass powder / strength of benchmark specimen) × 100%.
[0030] The activity index is obtained by measuring the 28d±2d compressive strength ratio of mortar mixed with waste glass powder, and the mixing amount of the waste glass powder is 20%-40%.
[0031] Compared with the prior art, the advantages of the present invention are:
[0032] The method for rapid evaluation of waste glass activity based on dissolution kinetics analysis proposed in the present invention significantly shortens the test period from the traditional 28 days to 24 hours, greatly improving the detection efficiency. The method establishes a scientific and complete "particle size-reaction rate-activity index" evaluation system, and achieves a comprehensive characterization of its activity by accurately measuring the dissolution characteristics of waste glass in an alkaline environment. Experimental verification shows that the error between the predicted results and the measured values of this method is always kept within 2%, which fully meets the requirements of engineering applications.
[0033] The evaluation method adopted by the present invention is simple to operate, has low equipment requirements, and is easy to standardize and promote. Compared with traditional methods, the present invention significantly reduces the test cost and reduces the human and material investment in the preparation and maintenance of specimens. At the same time, the method has good versatility and is suitable for the activity evaluation of waste glass from different sources and different components, providing a reliable quality control method for the engineering application of waste glass. As an innovative evaluation method, the present invention not only solves the problems of long cycle and poor stability existing in traditional methods, but also provides important technical support for the resource utilization of waste glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the relationship between the glass powder particle size and the reaction rate constant.
[0035] Figure 2 This is the relationship between the 24h glass powder silicon dissolution amount S24 and its activity index K.
[0036] Figure 3 This is the relationship between the reaction rate constant k and the activity index K. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples of the specification. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0038] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0039] Example 1: Study on the dissolution kinetics of waste glass with different particle sizes
[0040] The preparation of waste glass samples is a key step to ensure the accuracy of the evaluation results. In the pretreatment stage, the waste glass is first rinsed with tap water three times to remove surface dirt and impurities; then the sample is immersed in acetone for 10 minutes to remove residual organic matter on the surface; then it is repeatedly rinsed with deionized water three times to ensure that the sample surface is clean; finally, the sample is placed at 105±5℃ and dried for 24 hours to constant weight.
[0041] After pretreatment, the waste glass is initially crushed using a jaw crusher, and the crushed particles must pass through a 40-mesh standard sieve. Fine grinding is then carried out, and a ball mill is used for powder grinding. The ball-to-material ratio is strictly controlled at 4:1. Zirconia balls are used as ball milling media, and the ball milling speed is set to 200r / min. In order to obtain samples of different particle sizes, the ball milling time needs to be precisely controlled: 6μm samples require ball milling for 120 minutes, 11μm samples require ball milling for 60 minutes, 19μm samples require ball milling for 40 minutes, 25μm samples require ball milling for 20 minutes, and 38μm samples require ball milling for 10 minutes. After ball milling, the particle size test is immediately carried out to ensure that the sample particle size meets the requirements.
[0042] Each step of the above preparation process needs to be strictly controlled to ensure the stability and comparability of sample quality and provide a reliable experimental basis for subsequent activity evaluation.
[0043] Abandoned glass bottles were selected, and their main chemical composition (mass fraction, %) was: SiO2 (71.3%), Al2O3 (1.8%), CaO (10.2%), Na2O (13.5%), and others (3.2%). They were prepared into 5 samples with different particle sizes: 6μm, 11μm, 19μm, 25μm, and 38μm. The dissolution test was carried out at 40℃, and the silicon dissolution rate at each time point from 0 to 24h was measured as shown in Table 1:
[0044] Table 1 Silicon dissolution rate of waste glass with different particle sizes (%)
[0045] Time (h) 6μm 11μm 19μm 25μm 38μm 0.25 3.27 3.02 1.84 1.43 0.97 0.5 3.94 3.68 2.28 1.39 0.84 1 6.82 5.41 3.94 1.66 1.25 3 9.39 7.92 5.08 2.48 1.79 6 12.46 9.91 6.59 3.56 2.57 24 25.71 13.91 8.68 5.48 2.59
[0046] The apparent first-order reaction kinetic equation ln(1-α)=-kt was adopted, where α is the silicon dissolution rate and t is the reaction time (h). The dissolution data of 0-24h were fitted, and the reaction rate constants k of samples with different particle sizes were obtained: 6μm: k=0.0152h-1(R2=0.986); 11μm: k=0.0075h-1(R2=0.984); 19μm: k=0.0045h-1(R2=0.979); 25μm: k=0.0028h-1(R2=0.975); 38μm: k=0.0016h-1(R2=0.968
[0047] Example 2: Establishing the Dissolution Kinetics-Particle Size Relationship
[0048] The fitting results of k and d are shown in Figure 1 , we get the relationship: k = 0.0335d -1.52 This relationship shows that there is a significant power function relationship between the reaction rate constant k and the particle size d, which can be used to predict the reaction activity of waste glass with different particle sizes.
[0049] Example 3: Establishing a quantitative evaluation model
[0050] Combined with the known 28d activity index data: 6μm: K = 96%; 11μm: K = 85%; 19μm: K = 79%; 25μm: K = 75%; 38μm: K = 70%
[0051] 1. The 24h dissolution rate (S 24 ) and 28d activity index (K) were subjected to linear regression analysis, and the result was: K = 1.1S 24 +68.7 Where: K is the 28d activity index (%), S 24 The correlation coefficient of 24h dissolution rate (%) is R2 = 0.988, indicating that the two have a significant linear correlation (such as Figure 2 shown), Figure 2 The feasibility of accurately predicting the 28-day activity index by the 24-hour dissolution rate was verified.
[0052] 2. Linear regression analysis of the reaction rate constant (k) and the 28d activity index (K) yielded: K = 1809.9k + 69.6, where K is the 28d activity index (%), k is the reaction rate constant (h-1), and the correlation coefficient R2 = 0.97, indicating a good fitting effect (e.g. Figure 3 shown), Figure 3 The reliability of using kinetic parameters to evaluate the activity of waste glass was confirmed.
[0053] Figure 1 to Figure 3 Together they constitute a complete evaluation system of the present invention, demonstrating the quantitative relationship among particle size, dissolution characteristics, kinetic parameters and activity index, and providing a theoretical basis for the rapid evaluation of waste glass activity.
[0054] Example 4: Evaluation system verification
[0055] A waste glass (SiO2, 72.1%; Al2O3, 1.7%; CaO, 9.6%; Na2O, 13.6%; other 3.0%) was selected and prepared into three samples with different particle sizes: T1: 9μm; T2: 15μm; T3: 28μm. The dissolution test was carried out at 40℃, and the results are as follows:
[0056]
[0057] The results show that the relationship between k value and particle size d is consistent with k = 0.0355d -1.52 ; The relationship between k value and activity index K is consistent with K = 1809.9k + 69.6; The relationship between 24h dissolution rate and activity index K is consistent with K = 1.1S 24 +68.7. The results of the three prediction methods are consistent with each other, and the errors with the measured values are all less than 2%.
[0058] The above results show that: the prediction based on the quantitative relationship between the 24h dissolution rate and the 28d activity index is accurate; the quantitative relationship between the reaction rate constant and the 28d activity index is reliable; and the evaluation system established in the present invention has good practicality.
[0059] It should be understood that the above detailed description of the technical solution of the present invention with the help of optimized embodiments is illustrative rather than restrictive, and it cannot be determined that the specific implementation methods of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, modifications to the technical solutions recorded in the embodiments, or equivalent replacement of some of the technical features therein, should be deemed to fall within the scope of patent protection determined by the claims submitted for the present invention.
[0060] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis, characterized in that: The following steps are involved: (1) Preparation of waste glass samples; (2) Dissolution test in alkaline environment; (3) Dissolution kinetics analysis; (4) Establishing an activity evaluation system; In step (2), the conditions of the dissolution test in the alkaline environment include: NaOH solution concentration: 2-6 mol / L; solid-liquid ratio of waste glass to alkaline solution: 1:300-1:600 g / mL; temperature range: 20-60° C.; stirring speed: 800-1200 rpm; In step (3), the dissolution kinetic analysis includes: using ICP-OES to measure the concentration of dissolved ions, calculating the dissolution rate, establishing a kinetic equation, and finally determining the reaction rate constant; In step (4), the activity evaluation system includes: establishing the relationship between kinetic parameters and particle size, establishing the relationship between dissolution characteristics and activity index, and determining the activity classification standard.
2. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 1, characterized in that: The waste glass sample preparation comprises: (1) Cleaning and drying; (2) ball milling to prepare samples with different particle sizes; (3) Determination of chemical composition; (4) Control the specific surface area.
3. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 2, characterized in that: Specifically: (1) First, pre-treat the waste glass: clean the waste glass, dry it at 105±5℃ to constant weight, and then crush it preliminarily; (2) Then, the powder was ground using a ball mill. By controlling the grinding time, samples with different particle sizes were obtained, including five specifications of 6 μm, 11 μm, 19 μm, 25 μm, and 38 μm. The D 50 Ensure that the particle size meets the requirements and the ground sample is dried at 105±5℃; (3) Finally, component analysis was performed, and the chemical composition was determined using an X-ray fluorescence spectrometer, recording the contents of the main oxides SiO2, Al2O3, CaO, and Na2O.
4. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 1, characterized in that: In step (2), the alkaline environment is an alkaline solution environment.
5. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 4, characterized in that: The alkaline solution is a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution or a lithium hydroxide solution.
6. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 1, characterized in that: Step (2) is specifically as follows: When preparing the solution, first weigh analytical pure NaOH, prepare it into a 4 mol / L solution with deionized water, and cool it to the test temperature at room temperature; The test conditions are as follows: solid-liquid ratio is 1:300-1:600 g / mL, 1.0000±0.0005 g of waste glass powder is accurately weighed, and 500±1 mL of NaOH solution is added; the test is carried out at 40°C, and the magnetic stirring speed is controlled at 1000±50 rpm; Sampling was carried out at specified time points, including 0.25h, 0.5h, 1h, 3h, 6h, 12h, and 24h; 10mL of sample was taken each time, filtered using a 0.45μm filter membrane, and then diluted with a 5wt.% nitric acid solution, with the dilution multiple selected from 10 to 50 times according to the concentration; the diluted filtrate samples were stored in a refrigerator at 5±1℃.
7. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 1, characterized in that: Step (3) is specifically as follows: ICP-OES was used to determine the silicon ion concentration in the filtrate, the silicon dissolution rate at different time points was calculated, and the dissolution data was subjected to kinetic analysis: The apparent first-order reaction kinetic equation is adopted: ln(1-α)=-kt Where: α is the silicon dissolution rate, t is the reaction time (h), and k is the reaction rate constant (h-1); For samples with different particle sizes, the reaction rate constant k is calculated by fitting; there is a power function relationship between the k value and the particle size d: k=A*d -n Where A and n are fitting constants.
8. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 1, characterized in that: Step (4) is specifically as follows: The raw materials include ordinary Portland cement, sand, the waste glass sample prepared in step (1) and tap water; According to the water-cement ratio of 0.5, the sand-cement ratio of 3, the waste glass powder replaces 20%-40% of the cement mass; the specimens are prepared according to the requirements of GB / T17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", and 40mm×40mm×160mm specimens are made, and 3 parallel specimens are prepared in each group; the stirring adopts slow stirring for 120±5s and fast stirring for 120±5s; the specimens are immediately covered with plastic film after forming, demoulding after 24±2h, and standard curing is carried out at a temperature of 20±2℃ and a relative humidity of ≥95%; After curing for 28 days, the compressive strength test was carried out, and the average value of 3 specimens was taken to calculate the activity index K = (strength of specimen mixed with 30% waste glass powder / strength of reference specimen) × 100%.
9. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 8, characterized in that: The compressive strength test is carried out according to the test method of GB / T 1596-2017 "Fly ash used in cement and concrete".
10. The method for rapid comprehensive evaluation of waste glass activity based on dissolution kinetics analysis according to claim 8, characterized in that: The activity index is obtained by measuring the 28d±2d compressive strength ratio of mortar mixed with waste glass powder, and the mixing amount of the waste glass powder is 20%-40%.
Citation Information
Patent Citations
Method for rapidly detecting activity of solid waste applied to building material
CN111189705A
Method for rapidly detecting activity index of fly ash
CN113985002A
Method for rapidly detecting activity index of mineral powder
CN115639061A
Method for rapidly determining active strength index of industrial solid waste volcanic ash
CN116908231A
Mineral admixture activity rapid prediction method based on artificial intelligence
CN118035693A
Cited By
Method for improving gelation activity of waste glass powder through physical and chemical synergistic activation
CN119461902A
Method for physical-chemical synergistic activation to improve cementitious activity of waste glass powder
CN119461902B
Method for determining influence of waste incineration bottom ash on mortar performance based on hyperspectral data
CN121364160A
Preparation method of ternary solid waste alkali-activated cementing material based on particle size regulation and control
CN121591429A
A method for preparing ternary solid waste alkali-activated cementitious materials based on particle size control
CN121591429B